Methodological approach in assessing sustainable development of regional economy - Golovanov Egor Borisovich (Sovremennye Tehnologii Upravleniâ, 2015)
The article deals with the essence of the content of sustainable development of regional economy. Peculiarities of the regional economy as a spatial aspect of human activity. Based on the study of scientific approaches and concepts to the understanding of the category "sustainability" and "sustainable development" is proposed clarification of the concept of sustainable development of regional economy. Disclosed methodical approach to the assessment that takes into account the influence of three subsystems: economic, environmental and social impact on the sustainable development of regional economy. Proposed matching algorithm, based on which we calculated the integrated indicator of sustainable development on the example of the Chelyabinsk region, the interpretation of the results.